Terminological Classification of Names of Work Tools: A Comparative Study of English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The evolution of work tools reflects human ingenuity and cultural diversity, and their names are a rich source of linguistic and cultural insights. This paper examines the terminological classification of work tool names in English and Uzbek, highlighting their linguistic structures, semantic features, and cultural contexts. By analyzing examples from both languages, the study identifies functional, material-based, and cultural-historical classifications. Additionally, it explores the role of loanwords, metaphorical usage, and idiomatic expressions in shaping these terms. The findings underscore the interplay between language, technology, and culture, offering insights valuable for linguistics, translation, and cross-cultural studies.